Efektivitas Metode Self-Writing Living Book Terintegrasi Deep Learning Terhadap Keterampilan Menulis Kreatif Pengalaman Best Practice dan 6Cs Global Competences - Wiki Tedi Rahmawati; Yunita Mutiara Harahap; Aisyah Risti Wardani (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
The development of creative writing skills plays a vital role in fostering critical thinking, effective communication, and advanced literacy. Meanwhile, the 6Cs Global Competencies (critical thinking, creativity, communication, collaboration, character, and citizenship) form the core foundation of the Deep Learning approach which aims to shape globally competitive individuals. This research evaluated the effectiveness of the Self-Writing Living Book method, integrated with Deep Learning in enhancing students' creative writing skills while supporting the growth of the 6Cs competencies. Utilizing a mixed-methods approach, quantitative data was used to assess creative writing abilities, while qualitative data explored the method’s contribution to developing global competencies. Research findings revealed a significant improvement in post-test scores, particularly in elements such as characterization, plot structure, and linguistic style which demonstrating the method’s success in facilitating authentic creative expression. Observations and interviews showed that students experienced growth in character, communication, and collaboration through reflective processes. However, several challenges persisted, including difficulties in initiating writing, constructing narratives, and managing time effectively. The success of the Deep Learning approach largely depends on a supportive learning environment and the empathetic role of the teacher as a facilitator. Overall, this method proves effective in enhancing both students’ skills and learning motivation.